Increased levels of IL‐21 responses are associated with the severity of liver injury in patients with chronic active hepatitis B. Issue 9 (10th March 2014) - Pan, Q.; Yu, Y.; Tang, Z.; Xi, M.; Jiang, H.; Xun, Y.; Liu, X.; Liu, H.; Hu, J.; Zang, G.
Summary Interleukin‐21 (IL‐21) participates in tissue damage in various immune‐mediated diseases. Its role in the pathogenesis of chronic active hepatitis B (CAHB) has not been clarified. The frequency of circulating IL‐21+ T cells and the levels of serum and intrahepatic IL‐21 have been characterized in 70 CAHB patients, 32 inactive carrier (IC), 18 chronic hepatitis C (CHC) and 20 healthy controls (HC). Their potential association with liver injury was analysed. The percentages of IL‐21+CD3+CD8− and IL‐21+CD3+CD8+ T cells and the levels of serum IL‐21 in CAHB patients were significantly higher than that in the IC, CHC patients and HC (P < 0.001) and were correlated positively with the levels of serum alanine aminotransferase (ALT, r = 0.424, P < 0.001; r = 0.392, P = 0.001) and aspartate aminotransferase (AST, r = 0.388, P = 0.001; r = 0.329, P = 0.005) in CAHB patients, respectively. The levels of IL‐21 expression in the liver tissues were associated significantly with increased degrees of inflammation and fibrosis in CAHB patients (P < 0.01 or P < 0.05). Our findings suggest that aberrant IL‐21 responses may be associated with the progression of CHB.